Management strategies for dive sites in Bunaken Island (North Sulawesi, Indonesia), based on stakeholder’s perceptions - Kamagi, Jongky W.A.; Schaduw, Joshian N.W.; Lasut, Markus T. (AQUATIC SCIENCE & MANAGEMENT, 2016)
Title (Bahasa Indonesia): Strategi pengelolaan untuk daerah penyelaman berdasarkan persepsi stakeholder di Pulau Bunaken, Sulawesi Utara, Indonesia Bunaken Island is one of the island located in the Bunaken National Park, North Sulawesi, Indonesia. Most of the diving activities are in the waters of Bunaken Island, in which the management involves stakeholders (public, tourists, policy makers, NGOs, and academia). This study used questionnaires as a research instrument to obtain primary data, while secondary data were used as a complement to formulate an alternative strategy, using SWOT analysis. Based on the stakeholders’ perception, dive site management strategies covered research development on environmental issues, regulation availability, carrying capacity and information, community empowerment in addressing environmental problems, coordination among stakeholders for institutional issues and the environment, and improvement of service managing institutions in terms of organizational management and risk management. The study recommended the need for a clear management strategy, the necessity of doing research for regional development strategies/ locations for both diving and other potentials, the need of good marketing strategy, and the need for tourism activities diversification. Pulau bunaken merupakan salah satu pulau yang berada di dalam Taman Nasional Bunaken, Sulawesi Utara, Indonesia. Sebagian besar aktivitas penyelaman berada di Pulau Bunaken di mana dalam pengelolaannya melibatkan stakeholder (masyarakat, wisatawan, pengambil kebijakan, LSM, dan akademisi). Penelitian ini menggunakan instrumen kuesioner sebagai alat pengumpul data primer; data sekunder dikumpulkan sebagai pelengkap untuk merumuskan alternatif strategi, menggunakan analisis SWOT. Hasil analisis menunjukkan, secara umum, bahwa strategi pengelolaan daerah penyelaman, berdasarkan persepsi stakeholder, meliputi: pengembangan penelitian untuk isu-isu lingkungan; ketersediaan regulasi, pengelolaan pengunjung (daya dukung) dan informasi; pemberdayaan masyarakat dalam mengatasi masalah lingkungan; koordinasi antar stakeholder untuk isu-isu kelembagaan dan lingkungan; dan peningkatan pelayanan lembaga pengelola dalam hal manajemen organisasi maupun manajemen resiko. Penelitian ini merekomendasikan perlu adanya strategi pengelolaan yang jelas, perlu dilakukan penelitian untuk strategi pengembangan daerah/lokasi untuk objek wisata baik wisata selam maupun wisata lainnya, perlu strategi pemasaran yang baik, dan perlu diversifikasi aktivitas kegiatan pariwisata.